EVALUATION OF SERUM γ-GLUTAMYL TRANSFERASE AND ITS ASSOCIATION WITH HIGH SENSITIVITY C-REACTIVE PROTEIN AND INSULIN LEVELS IN THE PATIENTS WITH METABOLIC SYNDROME - Dharuni, R.; Maruthi Prasad, B. V.; Vishwanth, H. L. (International Journal of Medicine and Medical Research, 2019)
Background. Metabolic syndrome (MS), a collection of cardiovascular risk factors, is a major worldwide public health problem. The gathered data prove that serum gamma-glutamyl transferase (γGT) activity is a true marker of atherosclerotic cardiovascular disease (CVD) and is of a prognostic importance as well as the high-sensitivity C-reactive protein (hs-CRP). Objectives. In the study, we sought to evaluate serum γGT activity, hs-CRP and insulin resistance in patients with MS. Methods. The study involved 50 persons with metabolic syndrome and 50 healthy age and sex matched controls. Fasting serum samples of all participants were investigated for γGT, hs-CRP, insulin, blood glucose, lipid profile and liver function tests. Anthropometric measurements and BMI were also calculated Results. In that case 50% showed significantly high γGT compared to the controls, 30% proved increased hs-CRP levels above >0.5 mmol/L, whereas 94% of the controls were within the reference range. 74% of cases revealed the presence of insulin resistance while 32% of the controls showed insulin resistance. High γGT levels were also observed in that case with deranged lipids levels and high BMI. Conclusions. The study suggests that the patients with MS have a higher serum γGT activity. This study also proves that hs-CRP and HOMA-IR, which are independent risk factors of CVD, are also associated with MS. The correlation between γGT and the components of MS are also found significant compared to hs-CRP. Thus, γGT can be considered as an inexpensive and authentic predictor of MS, which can be a manifestation of CVD in near future.